(untitled) (Ustozlar uchun, 2026)
This article explores the significant role of translation as a bridge between languages and cultures in the modern globalized world. Translation is viewed not only as a linguistic process but also as a cultural and communicative activity that enables the exchange of ideas, values, and traditions among different societies. The paper analyzes the importance of translation in fostering intercultural communication, promoting mutual understanding, and preserving cultural identity. It also discusses the major challenges translators face, including cultural differences, idiomatic expressions, and the problem of equivalence. Furthermore, the study examines various translation strategies used to overcome these difficulties. The findings suggest that successful translation requires both linguistic competence and cultural awareness.